Budget Revenues in Poland During the Financial Crisis of 2007 and the Covid-19 Pandemic - Wierzbicka, Wioletta; Kalitka, Zuzanna (Olsztyn Economic Journal, 2023)
Maintaining sound public finances is a key aspect of the proper functioning of a country’s economy and its future development. This condition depends on the level of expenditure and revenue generated. Effective management of state revenues is therefore of the utmost importance. Importantly, the level and structure of government revenues depend on many factors, including exogenous factors such as crises. The global financial crisis of 2007 and the crisis caused by the Covid-19 pandemic had a significant impact on the level of budget revenues in Poland. The aim of the study was to assess the level and dynamics of changes in the state budget revenues in Poland in the years 2007-2021. Research shows that the financial crisis of 2007 had a much stronger impact on the level of budget revenues in Poland and the structure of revenues than the crisis caused by the Covid-19 pandemic. The research hypothesis, which assumed that the outbreak of the Covid-19 pandemic caused a stronger impact on the level of budget revenues in Poland than the global financial crisis of 2007 was thus negatively verified.